Perspectives on innovation - Malerba, Franco, 1950-.; Brusoni, Stefano (Cambridge, UK ; New York Cambridge University Press, 2007)
Innovation has become a major field of study in economics, management, sociology, science and technology, and history. Case studies, empirical models, appreciative analyses and formal theories abound. However, after several decades of study on innovation, and so many different types of contribution, there are still many phenomena we know very little about. The debate on innovation still has much to deliver; important questions remain unanswered and many problems require solution. Bringing together many leading figures in the field, this collection aims to address these concerns by offering detailed analyses of topics that are crucial for understanding innovation. In addition, it offers discussions of topics that researchers are just beginning to explore and of topics that continue to defy our efforts to understand and systematise. This important and wide-ranging collection will be essential reading for academic researchers and graduate students who wish to gain a broad overview of frontier-research in innovation.
Keywords: Technological innovation -- Economic aspects; Technological innovation -- Social aspects